Daily corticosterone rhythm modulates pineal function through NFκB-related gene transcriptional program - Da Silveira Cruz-Machado, Sanseray; Tamura, Eduardo K.; Carvalho-Sousa, Claudia E.; Rocha, Vanderlei Amadeu; Pinato, Luciana [UNESP]; Fernandes, Pedro A. C.; Markus, Regina P. (Springer Nature, 2017)
Melatonin and glucocorticoids are key hormones in determining daily rhythmicity and modulating defense responses. In nocturnal animals, corticosterone peaks at light/dark transition,while melatonin peaks at the middle of the night in both nocturnal and diurnal animals. The crosstalk between adrenal and pineal glands under inflammatory conditions indicates that corticosterone potentiates nocturnal melatonin synthesis by reducing the activity of NFκB. This transcription factor, which modulates the expression of a key enzyme in melatonin synthesis, is sharply reduced at the entrance of darkness in the rat pineal gland. In this study, we established the basis for understanding the crosstalk between adrenal and pineal glands in physiological conditions. Here we show that the expression of 70 out of 84 genes implied in defense responses exhibit a sharp reduction exactly at the entrance of darkness. Mifepristone impair the changes of 13 out of 84 genes, suggesting that the rhythm of corticosterone modulates pineal phenotype, as mifepristone also reduces the expression of Aanat and the nocturnal synthesis of melatonin. Therefore, darkness-induced synthesis of the pineal hormone, besides being controlled by the central clock located in the hypothalamus, is also influencedby glucocorticoids through the regulation of NFκB transcriptional program.